2012
DOI: 10.1136/bjsports-2011-090896
|View full text |Cite
|
Sign up to set email alerts
|

Sickle cell trait associated with a RR of death of 37 times in national collegiate athletic association football athletes: a database with 2 million athlete-years as the denominator

Abstract: BackgroundThis study examines sickle cell trait (SCT) as a cause of sudden death in National Collegiate Athletic Association (NCAA) athletes and explores the cost-effectiveness of different screening models. Methods The authors reviewed the cause of all cases of sudden death in NCAA student-athletes from January 2004 through December 2008. The authors also explored the cost-effectiveness of screening for this condition in selected populations assuming that identifying athletes with SCT would prevent death. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
105
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(106 citation statements)
references
References 25 publications
0
105
1
Order By: Relevance
“…That we did not find a difference using data from the CARDIA study is particularly important, given the young age of the cohort at the start of the study and the frequent description of exertion-related sudden death in young student athletes with SCT. 7 Data from largescale observational studies, including the National Health and Nutrition Examination Survey and Health, Risk Factors, Exercise Training and Genetics studies, have demonstrated lower fitness, measured directly by maximal tests or estimated from submaximal tests, in African American individuals when compared with their Caucasian counterparts. 36,37 However, it is more likely that lower levels of physical activity and higher BMI, which may affect muscle oxidative potential, contribute to disparities in fitness between African Americans and Caucasians.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…That we did not find a difference using data from the CARDIA study is particularly important, given the young age of the cohort at the start of the study and the frequent description of exertion-related sudden death in young student athletes with SCT. 7 Data from largescale observational studies, including the National Health and Nutrition Examination Survey and Health, Risk Factors, Exercise Training and Genetics studies, have demonstrated lower fitness, measured directly by maximal tests or estimated from submaximal tests, in African American individuals when compared with their Caucasian counterparts. 36,37 However, it is more likely that lower levels of physical activity and higher BMI, which may affect muscle oxidative potential, contribute to disparities in fitness between African Americans and Caucasians.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Growing evidence suggests SCT carriers may exhibit abnormal physiologic responses to cardiopulmonary exercise testing when compared with controls without SCT. [10][11][12][13] More recently, SCT status was also shown to be associated with a significantly higher risk for exertional rhabdomyolysis among black soldiers on active duty in the US Army.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…138 Unlike SD attributable to underlying cardiovascular disease and ventricular tachyarrhythmia, sickle cell trait-related collapse probably results from a more gradual deterioration and cascade of events, with intravascular sickling leading to vascular occlusion, endothelial damage, and impaired blood flow to muscles, which can promote ischemic rhabdomyolysis and disseminated intravascular coagulation. 138,169 In 2010, the NCAA mandated sickle cell trait screening (with solubility testing) for all student-athletes in Division I sports. 170 This program was created as part of a legal settlement with Rice University and the NCAA filed by the family of a college football player who died of exertional sickling with rhabdomyolysis at age 19 years.…”
Section: Other Screening Initiativesmentioning
confidence: 99%
“…That SCT can be responsible for lethal sudden collapse, 7 including on the athletic field, is based on evidence from the forensic-based US National Sudden Death in Athletes Registry 4,8,9 and other databases, 10 as well as numerous case reports and considerable expert experience acquired in athletic venues. 5 The epidemiology and characterization of SCTrelated events in athletes are evolving.…”
mentioning
confidence: 99%